2009
DOI: 10.1007/s11065-009-9116-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Genetic Research on our Understanding of Normal Cognitive Ageing: 1995 to 2009

Abstract: Identifying the risk factors for individual differences in age-related cognitive ability and decline is amongst the greatest challenges facing the healthcare of older people. Cognitive impairment caused by "normal ageing" is a major contributor towards overall cognitive deficit in the elderly and a process that exhibits substantial inter- and intra-individual differences. Both cognitive ability and its decline with age are influenced by genetic variation that may act independently or via epistasis/gene-environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 231 publications
(192 reference statements)
3
76
1
2
Order By: Relevance
“…In summary, considering previous observations, together with those of the present study, the influence of KIBRA or CLSTN2 SNPs on age-related memory performance is still questionable (Payton, 2009) and difficult to interpret (Milnik et al, 2012;Schneider et al, 2010). As the first longitudinal study to investigate the effects of these SNPs on memory and hippocampal volume we did not find support that these polymorphisms influence agerelated memory decline or hippocampal atrophy over two years in our cohorts of older adults.…”
Section: Discussioncontrasting
confidence: 85%
“…In summary, considering previous observations, together with those of the present study, the influence of KIBRA or CLSTN2 SNPs on age-related memory performance is still questionable (Payton, 2009) and difficult to interpret (Milnik et al, 2012;Schneider et al, 2010). As the first longitudinal study to investigate the effects of these SNPs on memory and hippocampal volume we did not find support that these polymorphisms influence agerelated memory decline or hippocampal atrophy over two years in our cohorts of older adults.…”
Section: Discussioncontrasting
confidence: 85%
“…As is common in behavioral genetic studies, the effect size observed in this study was relatively small (Payton, 2009;Barnett, Jones, Robbins, & Müller, 2007). Future studies are needed to replicate these findings in independent data sets to substantiate the association between suboptimal DA modulation and forgetting.…”
Section: Discussionsupporting
confidence: 53%
“…Indeed, rarely do such associations account for more than 2% or 3% of the variance in the trait (Plomin, DeFries, et al, 2013). As pointed out by several authors, these low effect sizes stand in clear contrast to those of heritability estimates from twin and adoption studies, which, for general cognitive abilities, are around 50% (e.g., Harris & Deary, 2011;Hunt, 2011;Payton, 2009;Plomin, DeFries, et al, 2013;Turkheimer, 2011;Turkheimer et al, 2003). The two sets of contrasting effect sizes are at the heart of the missing-heritability problem (Maher, 2008;Turkheimer, 2011).…”
Section: Discussionmentioning
confidence: 87%